Lumbar Ligamentum Flavum: Spatial Relationships to Surrounding Anatomical Structures and Technical Description of En Bloc Resection - Losiniecki, Andrew J.; Serrone, Joseph C.; Keller, Jeffrey T.; Bohinski, Robert J. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background One structure, the ligamentum flavum, nearly always encountered in lumbar spinal operations, has not been examined as an important anatomical landmark. In this context, we describe its relevance in corridors of small surgical exposures created by minimally invasive spinal approaches.Material and Methods In cadaveric and intraoperative dissections, we introduce a systematic technique for resection of this ligament and clarify its anatomical relationships with the exiting nerve roots, pedicles, facet capsule, and midline epidural fat. Fixed human cadaveric spines were harvested en bloc to maintain the lower thoracic to sacral segments. A single coronal cut through the anterior portion of the pedicles ensured that the dorsal elements were intact. Viewed from the operative microscope, photographs depict the ligamentum flavum at various intraoperative steps.Results The ligamentum flavum can undergo safe en bloc sequential resection that widely exposes the disc space for discectomy and interbody fusion. Its superolateral and inferolateral attachments are identifiable landmarks, effective in locating the exiting nerve roots. Corners of the L4–L5 ligamentum flavum mark the axillae of the exiting nerve roots (i.e., its superolateral corner marks the axilla of the L4 nerve roots, and its inferolateral corner marks the shoulder of the L5 nerve roots).Conclusion Our cadaveric and microscopic surgical dissections show the ligamentum flavum as seen in the new corridors of small surgical exposures during minimally invasive surgeries of the lumbar spine. Identifying this landmark, surgeons can envision the location of the nerve roots to help prevent their injury.
Keywords: ligamentum flavum; minimally invasive spine surgery; lumbar spine